Soft Power and Exchange Rate Volatility - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2015)
Standard models-based exclusively on macro-financial variables-have made little progress in explaining the behavior of exchange rates. In this paper, we introduce a neglected set of 'soft power' factors capturing a country's demographic, institutional, political and social underpinnings to uncover the 'missing' determinants of exchange rate volatility over time and across countries. Based on a balanced panel dataset comprising 115 countries during the period 1996-2011, the empirical results are generally robust across different estimation methodologies and show a high degree of persistence in exchange rate volatility, especially in emerging market economies. After controlling for standard macroeconomic factors, we find that the 'soft power' variables-such as an index of voice and accountability, life expectancy, educational attainment, the z-score of banks, and the share of agriculture relative to services-have a statistically significant influence on the level of exchange rate volatility across countries.